Acute effects of traditional and electronic cigarettes on palatal blood flow in smokers: A cross-over pilot study - Orsolya Vámos; Norbert Kulcsár; Barbara Mikecs; Kata Kelemen; Réka Kaán; Lilla Abafalvi; Elek Dinya; János Vág; Péter Hermann; Barbara Kispélyi (Elsevier, 2024)
Background: Smoking is a significant health hazard and contributes to cardiovascular and pulmonary diseases. It can increase postoperative complications during oral and maxillofacial surgery due to its topical effect on the oral mucosa. New alternatives to traditional tobacco products are gaining popularity, in particular, electronic cigarettes. Objectives: This pilot study investigated the acute effects of nicotine-containing and nicotine-free electronic cigarettes on palatal blood flow (PBF), and compared their effects to traditional cigarettes. Materials and methods: 14 medically healthy volunteers (8 males, 6 females, age: 34.7 ± 7.0) were recruited for the study. All patients (N = 14) were requested to smoke nicotine-containing (ECN) and nicotine-free electronic cigarettes (EC0) and a mouthpiece (end of a traditional cigarette) as a control sham smoking blind test (BT). EC users did not smoke a traditional cigarette (TC), resulting in 10 people in the TC group. Palatal blood flow was measured by Laser Speckle Contrast Imager before, immediately after, and 15 min after the exposures. Exhaled carbon monoxide (eCO) and carboxyhemoglobin (COHb) were measured before and immediately after smoking with a piCO+ Smokerlyzer machine. Results: In all groups, no significant differences were observed in the changes of palatal blood flow between time points. Exhaled carbon monoxide and carboxyhemoglobin were significantly higher in the traditional cigarette (TC) group compared to the nicotine-containing electronic cigarette (ECN) and nicotine-free electronic cigarette (EC0) groups, both before and after the exposure (p < 0.05). Conclusion: Acute use of either traditional or electronic cigarettes may have minimal impact on palatal blood flow, but additional studies are required to clarify their impact on the mucosa.